1999
DOI: 10.1159/000053972
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Extracellular Matrix in Human-Cytomegalovirus-Infected Cells and a Human Artery Organ Culture Model to Study Its Biological Relevance

Abstract: The influence of human cytomegalovirus (HCMV) on the transcription of 11 selected, representative extracellular matrix genes was investigated in cell culture. Northern blot hybridization indicated the downregulation of all mRNAs investigated. Based on our results and the known repression of other extracellular matrix transcripts and the β-actin transcription during HCMV infection, we suggest that one molecular mechanism contributing to the cytopathic effect may be the transcriptional downregulation of genes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…While HCMV suppresses the transcription and expression of components of the extracellular matrix in productive infection, preexisting components appear to persist (28,47). The Powerblot detects high levels of fibronectin in infected cells, consistent with the extracellular matrix surviving infection.…”
Section: Discussionmentioning
confidence: 80%
“…While HCMV suppresses the transcription and expression of components of the extracellular matrix in productive infection, preexisting components appear to persist (28,47). The Powerblot detects high levels of fibronectin in infected cells, consistent with the extracellular matrix surviving infection.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, CMV modifies a number of other cellular factors involved in angiogenesis and wound repair processes including adhesion molecules (ICAM-1, VCAM-1, VAP-1, and E-selectin,) and growth factors and receptors (TGF-β, PDGF-AA, VEGF, and PDGFR) (Shahgasempour et al 1997;Burns et al 1999;Zhou et al 1999;Inkinen et al 2003;Helantera et al 2005;Inkinen et al 2005;Reinhardt et al 2005a;Reinhardt et al 2005b;Helantera et al 2006). In addition, increased matrix metalloproteinase (MMP)-2 activity is observed in HCMV infected cells in conjunction with a reduction in matrix gene expression, resulting in a malleability to SMC migration, an alteration in vessel remodeling which promotes a vasculopathy (Schaarschmidt et al 1999;Reinhardt et al 2006). The upregulation of agents that initiate endothelial adhesion and those that promote wound healing provides a means for CMV to enhance the adherence and infiltration of inflammatory cells that drive vascular disease.…”
Section: In Vitro Models Of Hcmv Mediated Wound Healing and Angiogenesismentioning
confidence: 99%
“…Previous studies by us and by others have demonstrated the applicability of ex vivo organ cultures for the analysis of viral tropism within preserved 3-dimensional tissue structures in skin, lung, intestinal, arterial, cervical, and neuronal tissues (6,17,33,35,57). In the present study, we have employed a novel decidual organ culture for the ex vivo modeling of HCMV infection in the maternal-fetal interface.…”
mentioning
confidence: 90%